Kakovost mamografskih slik in doze pri mamografiji v Sloveniji - Zdešar, Urban (Radiology and oncology (Ljubljana), 1999)
Image quality is a cornerstone of effective early breast cancer detection. Besides optimization as a radiation protection principle requires that the dose to the patient is as lower as compatible with required image quality. Annual inspections of mammography installations in Slovenia include average glandular dose determination and the estimation of image quality using mammographic phantom. The results of the inpections in the period from year 1996 to 1999 showed that the technical quality of mammographic instations in Slovenia is comparable to the developed countries. Still there are some problems, underexposed images being the most common one. Quality control programs would solve at least some of the problems, but not even one mammographic installation has one at the moment.
Keywords: Breast neoplasms; Diagnosis; diagnostika; dojke; Mammography; mamografija; novotvorbe; Phantoms, imaging; Quality control; Radiation dosage; rak (medicina)